2013
DOI: 10.1016/j.chroma.2013.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Fast methodology for the reliable determination of nonylphenol in water samples by minimal labeling isotope dilution mass spectrometry

Abstract: "B H<=G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…18,19 It has also been reported that data obtained through the use of the “minimal labeling approach” require corrections by an isotope pattern deconvolution algorithm. 16,17 On the other hand, the limited availability and/or high price of other than d -labeled analogues may be a practical hurdle that prevents their widespread applications.…”
mentioning
confidence: 99%
“…18,19 It has also been reported that data obtained through the use of the “minimal labeling approach” require corrections by an isotope pattern deconvolution algorithm. 16,17 On the other hand, the limited availability and/or high price of other than d -labeled analogues may be a practical hurdle that prevents their widespread applications.…”
mentioning
confidence: 99%
“…Therefore, isocratic conditions were also tested. Based on our previous work 18,23 different percentages of methanol-water combinations, with and without ammonia and ammonium acetate as modiers, were evaluated. The best sensitivity was reached with a mobile phase consisting of 97% methanol-water with 0.01% ammonia since the presence of NH 4 Ac negatively affected the signal of BPA.…”
Section: Resultsmentioning
confidence: 99%
“…The ubiquitous presence of the selected compounds in all the laboratory material, included solvents, is probably the main challenge during the determination of EDCs at very low concentration levels. For this reason, and according to our previous experience, 18,23 all of the glass material was rinsed with acetone, methanol and hexane. Compared with previous work, rinsing with hexane was also added to the cleaning procedure due to some contamination observed aer rinsing only with the other two solvents.…”
Section: Cleaning Proceduresmentioning
confidence: 99%
“…Finally, the experimentally measured isotope distributions for the labelled compound were compared with the 100 convoluted distributions by linear regression analysis . Then, the ‘right’ isotope enrichment was selected as to that giving the minimum in the square sum of residuals (SSR) between the calculated and observed distributions.…”
Section: Methodsmentioning
confidence: 99%